THE ROLE AND PARTICIPATION OF WOMEN IN THE ECONOMIC SECTOR IN THE DIGITAL ECONOMY - Shermamatova Iroda Oybekovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article analyzes the impact of women on the economy in the context of digital transformation, what challenges and opportunities they face, as well as prospects for further development.